2013
DOI: 10.1186/1471-2202-14-75
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with agomelatine or venlafaxine reduces depolarization-evoked glutamate release from hippocampal synaptosomes

Abstract: BackgroundGrowing compelling evidence from clinical and preclinical studies has demonstrated the primary role of alterations of glutamatergic transmission in cortical and limbic areas in the pathophysiology of mood disorders. Chronic antidepressants have been shown to dampen endogenous glutamate release from rat hippocampal synaptic terminals and to prevent the marked increase of glutamate overflow induced by acute behavioral stress in frontal/prefrontal cortex. Agomelatine, a new antidepressant endowed with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…A number of studies have shown that exposure to various stressors differing in intensity and duration increases glutamate concentrations in different limbic brain regions including the hippocampus 4 - 7 , 51 , whereas antidepressant treatments block depolarization- or stress-evoked glutamate release 8 , 12 , 52 , 53 . Glutamate release in these studies was measured using in vitro synaptosomal 52 , 53 and slide preparations 54 or in vivo microdialysis techniques 4 - 7 , 51 . These findings have contributed to our knowledge of regulation of the glutamatergic system by stress and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that exposure to various stressors differing in intensity and duration increases glutamate concentrations in different limbic brain regions including the hippocampus 4 - 7 , 51 , whereas antidepressant treatments block depolarization- or stress-evoked glutamate release 8 , 12 , 52 , 53 . Glutamate release in these studies was measured using in vitro synaptosomal 52 , 53 and slide preparations 54 or in vivo microdialysis techniques 4 - 7 , 51 . These findings have contributed to our knowledge of regulation of the glutamatergic system by stress and antidepressants.…”
Section: Discussionmentioning
confidence: 99%
“…abolishes the restraint stress-induced increase in extracellular glutamate efflux in limbic structures such as the basolateral and central nuclei of the amygdala and the hippocampus (Reagan et al, 2012). As previously found with other antidepressants (Bonanno et al, 2005), chronic administration of agomelatine (40 mg·kg −1 , i.p., for 21 days) significantly reduced endogenous release of glutamate from hippocampal synaptosomes and decreased BJP Pharmacological properties of the antidepressant agomelatine the accumulation of SNARE (soluble N-ethylmaleimidesensitive fusion protein attachment protein receptor) complex, a key molecular effector of vesicle docking, priming and fusion at presynaptic membranes (Milanese et al, 2013). Long-term administration of antidepressants elicits adaptive changes in the functional status of mGlu receptors (Paul and Skolnick, 2003;Palucha and Pilc, 2007).…”
Section: Involvement Of the Glutamate Pathwaymentioning
confidence: 99%
“…This results in a line-shaped cephalalgia through migraine pain pathway, as CSD-induced long-lasting activation of meningeal nociceptors innervated by the fibers of SON or GON has been accepted to be one of the original migraine pathophysiological processes leading to the activation of central trigemino-vascular neurons in the spinal trigeminal nucleus (C1-2) underlying migraine headache (Zhang et al 2010 ; Zhao and Levy 2015 ). This proposed pathogenesis related to CSD is seemly supported by the effective responses to anti-migraine drugs of flunarizine, venlafaxine, and anti-epileptic drug of sodium valproate which had been shown able to suppress CSD (Wauquier et al 1985 ; Ayata et al 2006 ) or reduce depolarization-evoked glutamate release (Musazzi et al 2010 ; Milanese et al 2013 ), basis of CSD which is a common therapeutic target for currently prescribed migraine prophylactic drugs (Costa et al 2013 ). This proposed pathogenesis is further supported by our recent case study of a woman who had a recurrent head pain circumscribed in a coronal line-shaped area around the head, a coronal LH.…”
Section: Discussionmentioning
confidence: 98%